AN ANALYSIS OF ILLOCUTIONARY ACT ON SONG LYRICS OF BRUNO MARS’S DOO-WOOPS & HOOLIGANS ALBUM - Ambar Wulan Sari; Tengku Winona Emelia (JGK (Jurnal Guru Kita), 2022)
An Analysis Of Illocutionary Act On Song Lyrics Of Bruno Mars’s Doo-Woops & Hooligans Album. Illocutionary act is an act performed in saying something. Illocutionary acts is an utterance with some kind of function in mind. As a part of written language, literary works such as play, novel, film, short story, and song can also be analyzed by using illocutionary act theoryThe study discussed about the use of Illocutionary Act to determine the lyric of the song’s meaning. The objectives of this study were to : (1) To describe the types of illocutionary speech acts are contained on song lyrics Doo-Woops & Holligans Album. And (2) To find out the functions of the illocutionary act found in the song lyrics Doo-Woops & Holligans Album. This study applied a descriptive qualitative method to analyze the data. The source of the data was obtained from Bruno Mars’s Doo-Woops & Holligans Album. The data was taken the lyrics of 10 songs from Bruno Mars’s Doo-Woops & Holligans Album to find the types and functions of Illocutionary Act . The technique in analyzing the data was using the theory of Miles & Huberman, that is data condensation, data display, and conclusion drawing and verfication. There were then found out the song lyrics of Doo-Wops & Hooligans Album by Bruno Mars use most of representative illocutionary acts and the song lyrics of Doo- Wops & Hooligans Album by Bruno Mars use most of collaborative illocutionary acts’s function.